Abiotic and biotic factors affecting the denning behaviors in Asiatic black bears Ursus thibetanus - Yamamoto, Toshiaki; Tamatani, Hiroo; Tanaka, Junpei; Oshima, Gen; Mura, Serina; Koyama, Masaru (Journal of mammalogy, 2016)
For bears, numerous associations between biotic and abiotic factors have been reported to correlate with the timing of den entry and emergence; however, an analysis showing which factors influence the timing of den entry and emergence has not been performed enough. In this study, a generalized linear mixed model was generated using 66 entry dates for 26 females and 40 entry dates for 26 males, and 56 emergence dates for 26 females and 25 emergence dates for 18 males between 1999 and 2012. Regarding factors for den entry, the average temperature in November and mast production of Mongolian oaks were significant for both males and females. For the date of den emergence, the average temperature in March affected strongly. For males, good mast production of Mongolian oaks in the previous year was found to be associated with early den emergence. For females, the presence of newborns had a significant influence on their den entry and emergence. This study indicated that denning behavior appears to be regulated by several abiotic and biotic factors and regulation factors are sex specific.